Density Affects Gametophyte Growth and Sexual Expression of Osmunda cinnamomea (Osmundaceae: Pteridophyta) - HUANG, YAO-MOAN (Ann Bot, 2004)
• Background and aims To understand how gametophyte densities affect the sexual expression and sizes of Osmunda cinnamomea and to provide information on the density of growth needed to favour successful reproduction, fresh spores were sown at various densities and subsequent gametophyte growth was studied. • Methods Spores were sown and cultured in the laboratory. Subsequent gameophytes at different population densities were sampled and their sexual expression and sizes were recorded. • Key results One-year-old multispore cultures of the fern O. cinnamomea demonstrated that population density affected gametophyte growth and sexual expression. As density increased, gametophytes became significantly smaller and more slender. Female and asexual gametophytes dominated in populations of low and high densities, respectively. At intermediate population densities, hermaphroditic and male gametophytes were dominant. Female gametophytes were larger than gametophytes of all other types. Hermaphroditic gametophytes were larger than male gametophytes, which were larger than asexual gametophytes. Large gametophytes were wide-cordate, whereas smaller ones tended to be narrow-spathulate. • Conclusions Gametophyte size of O. cinnamomea is negatively related to the population density, which significantly affects gametophytes' sexual expression. The presence of unisexual and bisexual gametophytes at intermediate densities indicates that both intergametophytic and intragametophytic selfing may occur.